Photoconductive response correction for detectors of terahertz radiation - Castro-Camus, E; Fu, L; Lloyd-Hughes, J; Tan, H; Jagadish, C; Johnston, M (2008)
Photoconductive detectors are convenient devices for detecting pulsed terahertz radiation. We have optimized Fe+ ion-damaged InP materials for photoconductive detector signal to noise performance using dual-energy doses in the range from 2.5× 1012 to 1.0× 1016 cm-2. Ion implantation allowed the production of semiconducting materials with free-carrier lifetimes between 0.5 and 2.1 ps, which were measured by optical pump terahertz probe spectroscopy. The time resolved photoconductivity of the detector substrates was acquired as a function of time after excitation by 2 nJ pulses from a laser oscillator. These data, when combined with a deconvolution algorithm, provide an excellent spectral response correction to the raw photocurrent signal recorded by the photoconductive detectors. © 2008 American Institute of Physics.